IMPLEMENTASI METODE TUTOR SEBAYA UNTUK MENINGKATKAN PRESTASI BELAJAR MATA PELAJARAN MANAJEMEN LOGISTIK PADA PESERTA DIDIK KELAS XI MANAJEMEN LOGISTIK SMK NEGERI 1 TASIKMALAYA - Aipudin, Dudung (LPPM Universitas Bina Bangsa, 2024)
In teaching and learning activities, the methods often used by authors include the classical system lecture method by explaining through the medium of an LED projector. It is felt that this method no longer attracts the interest of students in class XI Logistics Management, SMK Negeri 1 Tasikmalaya. Therefore, the author carries out the learning process using the cooperative learning together learning method or model as the author has researched in the previous academic year. The results obtained do show positive results, but the author is not yet satisfied, so the author wants to try other learning methods or models, with the assumption and hope that they can be more effective in increasing students' activities and achievements in learning Logistics Management. The method used in this research is the classroom action method, while the research techniques used in the research are (1) observation techniques, (2) test techniques, and (3) interview techniques. In this research, the data source is students of class XI Logistics Management at SMK Negeri 1 Tasikmalaya for the 2022-2023 academic year. Meanwhile, the hypothesis used is that applying the Peer Tutor Method can improve activities and learning outcomes in the Logistics Management subject, Warehouse Management elements. Learning Outcomes (CP) implementing the goods receipt process for Class peer tutoring method, then students' achievement in the Logistics Management lesson for the Warehouse Management element of Learning Achievement (CP) implementing the goods receipt process can increase. This hypothesis is proven to be true and can be justified by data on the average score before improvement (Pre-Cycle), the average class score only reached 77.22. After improvements were made in two cycles through the peer tutoring method, the first cycle class average value increased to 81.81 and the second cycle increased significantly to an average of 86.63 points. Based on the results obtained from each cycle, it is proven that the application of the peer tutoring method can improve the learning achievement of class